Fabrication of a solution-processed IGZO/NiO p-n diode - Arjmandi, Nima; Seraj, Mohammad (Scientia Iranica. Transaction D, Computer science & engineering, electrical engineering, 2024)
The fabrication of a p-n diode is investigated using a fully solution-processed method. Indium Gallium Zinc Oxide (IGZO) ink was synthesized and deposited on a quartz substrate and annealed to form a thin film serving as an n-type semiconductor. A facile sol-gel method was used to deposit a lithium doped nickel oxide thin film (Li:NiO) as a p-type semiconductor. X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM) were employed to characterize the structural properties of Li:NiO and IGZO films. XRD analysis revealed a polycrystalline bunsenite structure in the Li:NiO films. Nanocrystalline grains were also observed on the surface morphology of the Li:NiO films. The XRD analysis indicated that the IGZO films were amorphous. However, SEM images demonstrate a variety of nanostructures in these films, including hexagons. The Li:NiO molar ratio was optimized to minimize series resistance of the diode. NiO had a carrier density of 7.8E13 cm- and mobility of 0.8 cm- /V.S, the highest mobility ever reported in a NiO film to our knowledge. The carrier density of IGZO was 2.5E16 cm- ,and its mobility was 0.95 cm-2/V.S. The fabricated diode exhibited a current ratio of 175 in on and off states and a reverse breakdown voltage of 3.5 V.